Establishing a Cost-Effective 3-Dimensional Printing Laboratory for Anatomical Modeling and Simulation: An Institutional Experience. Issue 3 (June 2021) - Clifton, William; Damon, Aaron; Nottmeier, Eric; Pichelmann, Mark
Abstract : Summary Statement: Three-dimensional (3D) printing is rapidly growing in popularity for anatomical modeling and simulation for medical organizations across the world. Although this technology provides a powerful means of creating accurately representative models of anatomic structures, there remains formidable financial and workforce barriers to understanding the fundamentals of technology use, as well as establishing a cost- and time-effective system for standardized incorporation into a workflow for simulator design and anatomical modeling. There are many factors to consider when choosing the appropriate printer and accompanying software to succeed in accomplishing the desired goals of the executing team. The authors have successfully used open-access software and desktop fused deposition modeling 3D printing methods to produce more than 1000 models for anatomical modeling and procedural simulation in a cost-effective manner. It is our aim to share our experience and thought processes of implementing 3D printing into our anatomical modeling and simulation workflow to encourage other institutions to comfortably adopt this technology into their daily routines.